Farmers' Digital Literacy under the Background of Digital Rural Construction: Concept and Framework Construction - WANG Xiaoyu, ZHANG Suluo (Nongye tushu qingbao xuebao)
[Purpose/Significance] In the context of the digital era and the construction of digital villages, digital literacy is crucial for farmers to contribute to rural revitalization and promote the structural transformation of the rural workforce. The defination of the concept and framework construction of farmers' digital literacy is an important basis for the assessment of farmers' digital literacy level, which is of great significance for the education and training of farmers' digital literacy, the promotion of farmers' quality development, and the revitalization of rural talented people. [Method/Process] This study uses the content analysis method to define the concept of farmers' digital literacy based on the perspective of "ability + quality". Farmers' digital literacy refers to digital rural construction, for instance, the ability to use intelligent equipment and digital technology to obtain, produce, use, evaluate, interact, share and innovate digital information, with security guarantee, ethics, and apply to rural life and production practice, so as to improve the quality and ability of digital income increase. Through comparative analysis, this paper reviews the typical and representative digital literacy frameworks at home and abroad, and uses Bloom's cognitive hierarchy theory to construct the farmers' digital literacy framework from the dimensional-level perspective, innovatively introducing farmers' professional skills as the first-level dimension, which is a new skill required to train new professional farmers and high-quality farmers. There is a need to introduce skills related to agricultural occupations. [Results/Conclusions] The framework includes 8 core dimensions of farmers' digital awareness, digital operation, digital information, digital social interaction, digital innovation, digital security, digital application and professional skills, as well as 21 secondary dimensions and several specific elements, including three levels of digital literacy: basic, intermediate and advanced. The basic level consists mainly of "awareness and understanding" and some simple operations with digital technology, tools and equipment. The intermediate level is mainly to be "able to use", which may vary according to individual goals and needs, and professional characteristics. The advanced level mainly refers to "active participation in practice", which can be innovative and practical in a specific area. In the continuum of basic, intermediate and advanced levels, farmers can self-assess against the framework level, providing a pathway for continuous learning and updating of literacy skills. The construction of farmers' digital literacy framework under the background of digital village construction can provide guidance for the formulation of relevant policies and evaluation scales, the updating of the cultivation system of high-quality farmers, and the improvement of farmers' digital literacy. Indeed, as a scientific exploration, the issue of farmers' digital literacy framework still has a huge space for exploration, and it needs to be evaluated by experts, improved from the perspective of farmers' subjects and pre-tested to verify its scientificity and applicability.